Republic of Moldova : Financial System Stability Assessment; Update. (IMF Staff Country Reports; Country Report, 2008)
This paper discusses key findings of the Financial System Stability Assessment (FSSA) on Moldova. The assessment reveals that vulnerabilities of the financial sector appear to be manageable. Stress tests on likely scenarios do not indicate major vulnerabilities for the banking system as a whole. Since the 2004 Financial Sector Assessment Program, the National Bank of Moldova (NBM) has made progress in identifying bank owners, an issue then flagged as a major vulnerability, but other financial supervisors have been considerably less successful in this respect.